Genomic population structure and local adaptation of the wild strawberry Fragaria nilgerrensis. Issue 1 (19th January 2022) - Hu, Yuxi; Feng, Chao; Yang, Lihua; Edger, Patrick P; Kang, Ming
Abstract: The crop wild relative Fragaria nilgerrensis is adapted to a variety of diverse habitats across its native range in China. Thus, discoveries made in this species could serve as a useful guide in the development of new superior strawberry cultivars that are resilient to new or variable environments. However, the genetic diversity and genetic architecture of traits in this species underlying important adaptive traits remain poorly understood. Here, we used whole-genome resequencing data from 193 F. nilgerrensis individuals spanning the distribution range in China to investigate the genetic diversity, population structure and genomic basis of local adaptation. We identified four genetic groups, with the western group located in Hengduan Mountains exhibiting the highest genetic diversity. Redundancy analysis suggested that both environment and geographic variables shaped a significant proportion of the genomic variation. Our analyses revealed that the environmental difference explains more of the observed genetic variation than geographic distance. This suggests that adaptation to distinct habitats, which present a unique combination of abiotic factors, likely drove genetic differentiation. Lastly, by implementing selective sweep scans and genome–environment association analysis throughout the genome, we identified the genetic variation associated with local adaptation and investigated the functions of putative candidate genes in F. nilgerrensis.